Usefulness of Adjunctive Technique with a TACTICS Catheter for Coil Embolization of Cerebral Aneurysms - Masaki Takahara; Kenji Fukuda; Dai Kawano; Shintaro Yoshinaga; Hironori Fukumoto; Yoshinobu Horio; Mitsutoshi Iwaasa; Tooru Inoue (JNET, 2021)
Objective: We report the usefulness of the adjunctive technique using a 3.4-Fr TACTICS catheter, which is a distal access catheter (DAC) for coil embolization. Methods: Patients who underwent coil embolization with an adjunctive technique using a TACTICS catheter between October 2018 and May 2019 were retrospectively analyzed.Results: In all, 64 aneurysms in 51 patients were treated. Among them, 18 aneurysms in 15 patients (4 ruptured aneurysms and 14 unruptured aneurysms) required an adjunctive technique using a TACTICS catheter. The methods of embolization were the double catheter technique (DCT) for five aneurysms, stent-assisted coiling (SAT) for seven, DCT + SAC for one, and balloon-assisted technique (BAT) for five aneurysms. Aneurysms were located in the anterior communicating artery (Acom A) in three cases, distal anterior cerebral artery (dACA) in one, middle cerebral artery (MCA) in five, internal carotid artery (ICA) in six, basilar artery (BA) in one, and vertebral artery (VA) in two cases. It was easy to access distal intracranial vessels using the TACTICS catheter. In all cases, guiding of the microcatheter, coiling, and stent placement were improved. There were no complications associated with using the TACTICS catheter. Conclusion: Compared with conventional DACs, distal intracranial vessels were more easily accessed using the TACTICS catheter. A TACTICS catheter is useful because DCT and SAC require sufficient operability of the microcatheter.